2017
DOI: 10.1107/s2059798317004430
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy of chromatin biology

Abstract: The basic unit of chromatin, the nucleosome core particle (NCP), controls how DNA in eukaryotic cells is compacted, replicated and read. Since its discovery, biochemists have sought to understand how this protein-DNA complex can help to control so many diverse tasks. Recent electron-microscopy (EM) studies on NCP-containing assemblies have helped to describe important chromatin transactions at a molecular level. With the implementation of recent technical advances in single-particle EM, our understanding of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Local resolution is highest (~3.5 Å) for the histone octamer core, while DNA density on the outer perimeter tends to decrease (~4-4.5 Å), as observed previously for other NCP structures (Supplementary Figure 1) 2527 . Nevertheless, we could confidently model the DNA phosphate backbone for the entire assembly.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Local resolution is highest (~3.5 Å) for the histone octamer core, while DNA density on the outer perimeter tends to decrease (~4-4.5 Å), as observed previously for other NCP structures (Supplementary Figure 1) 2527 . Nevertheless, we could confidently model the DNA phosphate backbone for the entire assembly.…”
Section: Resultssupporting
confidence: 81%
“…These efforts led to describing the NCP architecture at an atomic level 79 , explained how DNA sequence can influence wrapping of the double helix 32 , and how common docking sites on the histone octamer are recognised by different interactors 3337 . Over the last four years, cryo-EM has started to provide a dynamic view of the NCP 25,3841 . Recent data indicated that NCPs are more flexible in solution, with the histone octamer visiting more compacted or extended states, compared with a nucleosome trapped in a crystal lattice 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrative approaches allow a variety of investigations on the dynamics of nucleosome and their associated protein factors—in particular, NMR, smFRET, SAXS, and AUC, as well as other biochemical/biophysical and computational biology techniques. [ 12,13,17,27,57,60,63,83 ]…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[ 8 ] More recently, cryo‐electron microscopy (cryo‐EM) has become extremely powerful, and has had notable success in the structural characterization of nucleosomes and several nucleosome‐bound complexes, as has been reviewed in the past. [ 9–12 ] Significant contributions to our understanding of these complex machineries and their dynamics have also come from the complementary biophysical techniques such as nuclear magnetic resonance (NMR) spectroscopy, [ 13–16 ] Förster resonance energy transfer (FRET), [ 17–19 ] small‐angle X‐ray scattering (SAXS), [ 15,20–23 ] small‐angle neutron scattering, [ 23 ] native electro‐spray ionization mass spectrometry, [ 21 ] size‐exclusion chromatography—multi‐angle light scattering (SEC‐MALS), [ 24,25 ] analytical ultra centrifugation (AUC), [ 16,24,26 ] and hydroxyl radical footprinting, [ 21,27 ] along with Molecular Dynamics (MD) simulation, modeling, and docking studies. [ 15–17,23,27 ] The different chromatin factors and viral proteins use specific features on the nucleosome such as the nucleosomal acidic patch, specific super‐helical locations, PTM marks, and the histone tails to interact with and modulate the nucleosome.…”
Section: Introductionmentioning
confidence: 99%
“…Hi-C (8,9), Micro-C (10) and other chromosome conformation capture methods (11,12) provide distance constraints as a measure of the large scale organization of chromatin structure. Super resolution microscopy (13,14) provides optical visualization of 3D structure at nanometer scale resolution, while electron microscopy (15), NMR (16), * To whom correspondence should be addressed. Tel: +1 318 257 5209; Fax: +1 318 257 4000; Email: bishop@latech.edu and X-ray crystallography (17) provideångström scale resolution of individual nucleosomes and nucleosome arrays.…”
Section: Introductionmentioning
confidence: 99%